Never Too Much—More talent in football (always) leads to more success - Long, A. M.; Graf, M.; Bilalic, M. (PLOS ONE, 2024)
Though it may appear counterintuitive, certain positive attributes can eventually have negative consequences when taken to an extreme. This concept is exemplified in sports, where an increase in talent among team members initially leads to improved success, but beyond a certain threshold, excessive talent can adversely affect the team. This occurrence is known as the Too Much Talent (TMT) effect, wherein status conflicts among highly skilled players can hinder team performance, particularly in sports that require coordination and cooperation. While early evidence supported the TMT effect in team sports, its validity has recently been challenged. In this study, we analyzed a comprehensive dataset consisting of 780 data points across 42 seasons from seven top European football (soccer) leagues to examine the TMT effect`s presence. Our findings reveal that football does not exhibit the TMT effect. Instead, we observed a consistent, positive correlation between the number of skilled players on a team and team success. Additionally, talent did not display diminishing returns, as its impact on success remained stable even at the highest concentrations of talent. We relate our results to existing theories and propose that future research comparing more individualistic and interdependent team sports could further enhance the field.